Considering the performance of psychopedagogical intervention from a focus of competitions (Original) (Revista científica Olimpia, 2021)
In the psychopedagogical formative process, you assume a highest space to the quality of the performance of the graduate to transform the educational reality. However, persist limitations in this specialist to implement psychopedagogical interventions that it be allowed approaching of simultaneous way and integrator all educational contexts. In consequence, in the present study psychopedagogical like integrative competition of the professional knowledge of the psychopedagogical in addition to indicators as from which the levels of development that are  caught up with at the construction of the same are  evaluated, sets itself a structure and functionality of intervention. These results emerge of projects, thesis of mastery and of doctorate of the authors, as part of his contribution to raise the quality of the performance of this professional in mail with the social and contextual present-day requests.
Keywords: formation, psychopedagogical intervention; professional knowledge; professional competition; professional performance